2002
DOI: 10.1016/s0885-3924(02)00508-0
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Anorexia–Cachexia Syndrome

Abstract: Other than weight loss, most traditional methods of nutritional assessment are not acceptable in advanced cancer patients because they are inaccurate, too expensive for routine use, or too difficult for a debilitated person to complete. The prognostic inflammatory and nutritional index (PINI) is a formula devised to evaluate nutritional status and prognosis in critically ill patients. It has been suggested that the PINI score can be used to follow most pathological conditions. It has been measured in several s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 22 publications
0
39
0
1
Order By: Relevance
“…This syndrome compromises quality of life and contributes to mortality. 10,11 Cancerassociated weight loss reflects activation of host catabolism with loss of muscle protein mass and body fat. As with other aspects of human cancer, this has been difficult to reproduce in animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This syndrome compromises quality of life and contributes to mortality. 10,11 Cancerassociated weight loss reflects activation of host catabolism with loss of muscle protein mass and body fat. As with other aspects of human cancer, this has been difficult to reproduce in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Tumor cell-and host-produced cytokines such as IL-6, TNF-␣ and IFN-␥ are thought to play an important role in the catabolism and weight loss associated with several malignant and nonmalignant conditions. 10,11,[17][18][19] However, the specific contribution of human tumor cell-secreted IL-6 to body weight loss has not been described. We hypothesized that neutralization of tumor cell-secreted IL-6 could inhibit body weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The development of cachexia is common in people with solid tumours such as pancreatic, lung, gastric and colorectal cancer. Cancer cachexia is associated with metabolic alterations that are likely to affect energy expenditure [7,8,9]. Patients with cancer cachexia are often malnourished; therefore, the provision of adequate nutrition support is essential for maintaining or improving nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the loss of adipose tissue accounts for the majority of the weight loss, but the loss of muscle accounts for most of the morbidity and mortality (13,14) . However, the extent of weight loss that is prognostic is not well defined (15,16) and performance status is recognised to be subjective (17) and therefore their reliability has been questioned.…”
mentioning
confidence: 99%